ANALISIS KADAR MAGNESIUM (Mg) TOTAL DAN MANGAN (Mn) PADA PENAMBAHAN EM4 TERHADAP PUPUK KOMPOS (SAMPAH KULIT KEDELAI - KACANG PANJANG) - Darius Ryan Partogi Simamora; Saibun Sitorus; Daniel Tarigan (PROSIDING SEMINAR KIMIA, 2022)
This study on composting time analysis and determining the optimum time based on pH conditions, temperature and humidity of soybean peel and string bean compost and determining the optimum variation of EM4 bioactivators to total magnesium (Mg) and manganese (Mn) levels has been carried out. The study consisted of making compost in takakura baskets, measuring the pH, temperature and humidity of the compost and analyzing total magnesium (Mg) and manganese (Mn) levels using an atomic absorption spectrophotometer. The results of measuring the pH, temperature and humidity of the compost were tested using a one-way analysis of variance test. The results showed that the F value of calculating the pH, temperature and humidity of the compost was greater than the table F value with successive values of 146.427 > 2.62; 10,690 > 2.62; 746.343 > 2.62 so it was concluded that the composting time had a significant effect on the pH, temperature and humidity of the compost. The optimum time of composting is 16 days with a pH of 7.19-7.5, a temperature of 27-28.9oC and a humidity of 50-60%. The optimum variation of EM4 is 5 mL with a total magnesium (Mg) content value of 0.09644% and manganese (Mn) total of 0.01788%.